PENGARUH TEKANAN EKSTERNAL, GAYA KEPEMIMPINAN DAN SISTEM PENGENDALIAN INTERNAL PEMERINTAH TERHADAP TRANSPARANSI LAPORAN KEUANGAN : (STUDI PADA PEMERINTAH DAERAH PROVINSI MALUKU) - Dirk Berly Tehuayo (P3M Politeknik Negeri Ambon, 2023)
This study aims to find out and test empirically the influence of external pressure, leadership style, the government's internal control system on the transparency of financial reports in the scope of the regional government of Maluku Province. This research was conducted on local government employees of Maluku Province. The type of data in this study is primary data, data collection was carried out by distributing questionnaires to regional financial managers in each SKPD of the regional government of Maluku Province with a total sample of 68 respondents. The sampling technique used purposive sampling method, namely sampling based on predetermined criteria. The data collection technique used is a survey technique using a questionnaire. Data analysis using multiple linear regression. The results of the study show that external pressure and the government's internal control system have a positive and significant effect on the transparency of financial reporting, while leadership style has not been able to influence the transparency of financial reports.Keywords: external pressure, leadership style, government internal control system, transparency of financial reporting.